Thermoneutral point analysis of ethanol dry autothermal reforming - Kale, Ganesh R.; Kulkarni, Bhaskar D. (Chemical Engineering Journal, 2010)
{Dry autothermal reforming of ethanol can be used to produce a variety of value added products like hydrogen, syngas and also carbon (possible CNF). A thermodynamic analysis of dry autothermal reforming of ethanol has been carried out to locate the thermoneutral temperatures and product composition at those points at 1, 3, 6 and 9 bar reaction pressures. The variations of thermoneutral temperatures and individual product yields at those temperatures have been discussed to find the optimum operating parameters for desired product output from the process. The process operated at thermoneutral conditions can give useful products like hydrogen, syngas (of low ratio) and carbon (possibly CNFs) and also provide a way for CO2 sequestration using renewable ethanol fuel. A maximum of 2.58 moles of syngas of ratio 2.01 obtained at 1 bar
Keywords: CO2 utilization; Dry autothermal reforming; Ethanol reforming; Thermoneutral